2021
DOI: 10.18502/ijph.v50i8.6819
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Quality Index and Cardiometabolic Risk Factors among Adult Women

Abstract: Background: The prevalence of cardiovascular disease is dramatically increasing particularly in developing countries. Among the different factors, diet has an important role in the pathogenesis of these diseases. This study aimed to assess the relationship between dietary quality index-international (DQI-I) and cardiovascular risk factors in adult Iranian women. Methods: This was a cross-sectional study of 371 participants, aged 20-50 yr, and recruited from 10 health centers from health centers affiliate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Adherence to DQI-I was associated with several metabolic parameters including BMI, WC, total cholesterol, Apo A/B, blood pressure, and uric acid, and DQI-I was confirmed as a good predictor of serum metabolic parameters in 1,404 adults from the Observation of Cardiovascular Risk Factors in Luxembourg (ORISCAV-LUX-2) study ( 14). Also, DQI-I was inversely correlated with BMI and serum total cholesterol and positively with high-density lipoprotein cholesterol (HDL-c) in other studies (20,27).…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Adherence to DQI-I was associated with several metabolic parameters including BMI, WC, total cholesterol, Apo A/B, blood pressure, and uric acid, and DQI-I was confirmed as a good predictor of serum metabolic parameters in 1,404 adults from the Observation of Cardiovascular Risk Factors in Luxembourg (ORISCAV-LUX-2) study ( 14). Also, DQI-I was inversely correlated with BMI and serum total cholesterol and positively with high-density lipoprotein cholesterol (HDL-c) in other studies (20,27).…”
Section: Discussionmentioning
confidence: 61%
“…Increased adiposity may further worsen their condition by exacerbating low and moderate inflammation and oxidative damage, as overweight and obese women with DOR have lower AMH levels compared to nonobese women with DOR (34). The association between DQI-I score and ovarian reserve may be mediated by inflammation or adiposity, as dietary quality indices were found to be inversely correlated with inflammatory markers and BMI in previous studies (14,27,35). In this regard, higher adherence to DQI-I and its components had a negative association with inflammatory markers including high-sensitivity C-reactive protein (hs-CRP) in a cross-sectional study on 200 Iranian overweight and obese women (36).…”
Section: Variablementioning
confidence: 90%
“…One study in Iranian female in Tehran, observed that DQI-I had no relationship with BMI or waist circumference [ 28 ]. However, in a study in Guatemalan adults showed a positive correlation of DQI-I with BMI and waist circumference [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…The DQI-I includes four scoring subgroups that examine complementary aspects of diet, i.e., variety, moderation, adequacy, and overall diet balance (Supplementary Tables 1 and 4) [ 13 , 14 ]. Studies have shown that the DQI-I correlated with several biomarkers associated with cardiometabolic risk factors, including inversely with total serum cholesterol, body mass index (BMI), and positively with high-density lipoprotein cholesterol (HDL-c), among others [ 14 16 ].…”
Section: Introductionmentioning
confidence: 99%